Variations of jump abilities in young soccer players in preparatory microcycles - Pivovarnicek, D.; Jurco, J. (Acta Kinesiologica, 2015)
The aim of the study was to compare performance confronted on jump abilities during these days of the week (Tuesday, Wednesday, Thursday andFriday) in the group of young soccer players (n = 10; age = 14.2 +/- years; height = 169.8 +/-0.9 cm; weight = 55.6 +/-0.2 kg) in microcycles of preparation period of I. competition year 2007/2008. Performance during single days was measured with a test . standing broad jump. Criterion of performance evaluation was distance.the length of standing broad jump with accuracy 1cm. Friedman test was used for determination of significance of differences in period under consideration. Nemenyi post-hoc test was used for determination of significance of differences in performance between single days. Statistical significance of differences in the study was determined at standardly used level = 0.05 with software IBMR SPSSR Statistics V19 and R Project. Friedman test has shown significant differences during period under consideration (X2 (3) = 13.701,p < 0.05, Kendall´s W = 0.23, effect size weak). Nemenyi post-hoc test has shown significant differences between Wednesday and Thursday, and Wednesday and Friday (p < 0.05). There were no significant differences between other days (p > 0.05).